Chinese Investments in Indonesia's Fintech Sector: Their Interaction with Indonesia's Evolving Regulatory Governance - Ajisatria Suleiman (Center for Indonesian Policy Studies (CIPS), 2019)
This paper analyses Chinese investment in the financial technology (fintech) sector in Indonesia, which ranges from payment systems to lending to wealth management. The paper calls for regulators to react to problems as they arise rather that controlling innovations to allow the market to meet consumer needs. It will specifically addresses fintech lending both by Chinese investors and their domestic partners as a major source of controversy in Indonesia. It elaborates on how Chinese investors respond to the evolving regulatory environment in Indonesia and addresses local debates over the intentions and structure of Chinese investors in the Indonesian fintech sector, comparing those debates to the actual situation of Chinese FDI in Indonesia.
Keywords: 330; Fintech; chinese investment; chinese; gojek; unicorn; financial technology; FDI; e-commerce; grab; OJK; lending; payment; microfinance; bukapalak; tokopedia; loan; payday loan; we chat; wechat; dana; airpay